PROSPECTIVE EVALUATION OF PRESCRIBING PRACTICES AND QUALITY OF LIFE OUTCOMES IN MIGRAINE PATIENTS - Dr Angel; Dr Neethu Mary; Dr Kailash Chander; Dr Siddharth Arjun Atwal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Migraine is amongst the most common disorders of the central nervous system affecting people throughout the world. Migraine can be managed to some degree by a variety of non-pharmacological and pharmacological treatment includes both acute and preventive therapy. Migraine has also been associated with poor health related quality of life (HRQoL). Such a study is important in India as there is insufficient data on impact of migraine on HRQoL and also the pattern of intake of various drugs associated with migraine. Material and methods: A total of 200 prescriptions of migraine patients were studied. Patient details were noted on case record form which included demographic information and details of disease. The demographic details and information on drug/drugs prescribed including dose, formulation and dosing frequency for acute as well as prophylactic treatment were noted. Results: The average number of drugs prescribed per prescription is in line with the WHO core indicators. The use of drugs for migraine prophylaxis had a significant improvement on the quality of life for study participants, based on the HIT-6 scores. At baseline, the mean HIT-6 score was 58.44. At the end of 3 months, the mean score had reduced to 51. A reduction in HIT-6 score indicates a decrease in severity and disability associated with migraine. There was a statistically significant difference between HIT-6 score at baseline and at 3 months. (p value <0.0001). Out of 200 prescriptions, drugs were prescribed by generic names in 70% (140) of the prescriptions. Out of a total of 657 drugs, 209 drugs were prescribed by generic names. The drugs prescribed by generic name were 31.81%. Conclusion: The prescribing pattern of drugs used for migraine was according to the guidelines. There is a potential for improving drug prescribing by generic name and drugs prescribed from essential drug list. The average number of drugs prescribed per prescription is in line with the WHO core indicators. The use of drugs for migraine prophylaxis had a significant improvement on the quality of life for study participants, based on the HIT-6 scores.